MCP-1 LEVELS AND ATYPICAL LYMPHOCYTES IN EARLY FEVER OF DENGUE VIRUS INFECTION WITH NON-STRUCTURAL PROTEIN 1 (NS-1) ANTIGEN TEST IN dr DARSONO HOSPITAL, PACITAN - Agustiningrum, Indah; Nugraha, Jusak; Kahar, Hartono (Institute of Topical Disease Universitas Airlangga, 2020)
Dengue infection caused by DENV and transmitted by mosquitoes Aedes aegypti and Aedes albopictus is a major health problem in the world, including Indonesia. Clinical manifestations of dengue infection are very widely, from asymptomatic until dengue shock syndrome (DSS). DENV will attack macrophages and dendritic cells (DC) and replicate them. Monocytes are macrophages in the blood (±10% leukocytes). Macrophages produce cytokines and chemokines such as monocyte chemotactic protein-1 (MCP-1)/CCL2. The monocytes that are infected with DENV will express MCP-1, which will increase the permeability of vascular endothelial cells so that they have a risk of developing DHF/DSS. Macrophages and DC secrete NS1 proteins, which are the co-factors that are needed for viral replication and can be detected in the early phase of fever. The increased MCP-1 levels in dengue infection followed by an increase in the number of atypical lymphocytes indicate the arrival of macrophages and monocytes to the site of inflammation which triggers proliferation rather than lymphocytes. This is an observational analytical study with a cross-sectional design to determine the MCP-1 level in dengue infection patients with 1st until the 4th day of fever and the presence of atypical lymphocytes. Dengue infection was determined by rapid tests NS1 positive or negative and MCP-1 levels were measured using by ELISA sandwich method.MCP-1 level of sixty patients dengue infection NS-1 rapid positive or negative with 2nd until 4rt fever were significantly higher than healthy subjects (420.263±158,496vs29, 475±23.443;p=0.000), but there was no significant difference in subjects with DF, DHF or DSS (436,47±225,59 vs422,77±170,55vs 448,50±117,39; p =0.844). Atypicallymphosite differs significantly in healthy subjects than subjects infected with DENV an average of 2% (p= 0,000). In conclusion, this shows the arrival of macrophages and monocytes to the site of inflammation, which triggers the proliferation of lymphocytes.